Optimalisasi Kompetensi Moral Anak Usia Dini - Masganti Sit (Jurnal Pendidikan dan Kebudayaan, 2010)
The objective of this research is to make early childhood’s moral competence optimally through the integrated learning based-moral model. The study was conducted at Tri Karya and Nusa Indah Kindergartens in Medan in the year of 2008 with n= 35. This action research was using Kemmis and Taggart model. The model has two cycles and each cycle has four steps. They are as follow (1) plan, (2) action, (3) observe and (4) reflect. To analyze the data, qualitative and quantitative were used. The result of the qualitative analyzes shows that the integrated learning based-moral model involved various activities, media and methods. The results of the quantitative analyze shows that there are significant differences between pre and post assessment of early childhood’s moral competence. To applying the integrated learning based-moral model was suggested to teacher, manager of early childhood education institution, researcher, government to plan, act, develop, and promote integrated learning based-moral model.